تصوف کے سلسلہ ’’امینیہ‘‘ کی علمبردار ’معراج العاشقین‘ کی اولین ترتیب و اشاعت - Shazia Umbreen; Hammad Rasool (Pakistan Journal of Islamic Research)
“Miraj-ul-Aashiqeen” was frist published by Maulvi Abdul Haq with muqadmma and Farhang from Hyderabad Deccan in 1343 Hijri. The subject of "Miraj-ul-Aashiqeen" is Sufism, whose poles go to the "Amina Family" and whose founder is Syed Shah Amin-ud-Din Alla. In the light of modern research, researchers are divided into two groups regarding the author of "Miraj-ul-Aashiqeen" and the first motivator of this difference of opinion is the Muqadamma of Maulvi Abdul Haq, written for "Miraj-ul-Aashiqeen". This book is of special importance in the history of Urdu literature due to its subject 'Sufism' and the orthodoxy of its language.